PENGEMBANGAN KAMPUNG ADAT SARIBU RUMAH GADANG SOLOK SELATAN SEBAGAI DAERAH TUJUAN WISATA - I Wayan Thariqy Kawakibi Pristiwasa (Jurnal Pariwisata Pesona, 2017)
I Wayan Thariqy Kawakibi Pristiwasa ?? Politeknik Pariwisata Batam, 1028098303 thariqy@btp.ac.id ABSTRACT This study aims to find the components in the development of indigenous villages saribu south gadang house as a tourist destination that is a strategic plan that can be developed for the development of tourism and improve the welfare of the community. This research uses descriptive qualitative research method with reference to the concept of tourism development. Population in this research is in the form of social situation with the participant that is in it that is Government and stakeholder of tourism, tourist and society. Intruments in this study are observation, and interviews using model coding, interpretation and congrulation. The results of this study indicate that the development of tourism can bring positive and negative impacts. Positive impacts can be seen in the improvement of the economy of the community around the tourist area and also contributes to the acquisition of local revenue. while negative impacts, among others: air pollution, water pollution, waste, Historical sites, and land use issues.